The accuracy of the Qur’anic systems in showing the graphic miracles - selected models -. - zeghad, lazhar (Journal of Social Sciences and Humanities, 2025)
The Holy Qur’an is considered the greatest book in rank and the most powerful influence on all of humanity. It is to it that the eyes are identified and the necks grow, and delving into it is the ultimate honor, as it is the miraculous speech of God in all respects, and perhaps the greatest of them is in terms of order and elucidation. The Arabs stood by the accuracy of its expressions and organized it with a confused and helpless pause, so he made them the argument and made them unable to respond and shut their mouths away from criticism, so they did not appear from them. The miraculousness and the statement of the power of Quranic rhetoric, especially after saying the pure in the Holy Quran. The rhetoric of the Qur’an, and the research answers the problem of its exhaustion: To what extent are the Qur’anic words capable of carrying the meanings of miraculousness? This is under the following title: “The accuracy of the Qur’anic systems in demonstrating the rhetorical miracles - selected models -, in order to identify the miraculousness of the Qur’an at the level of the letter, then the miraculousness of the Qur’an at the level of its pronunciation, then its miraculousness at the level of structures, with an indication of the importance and role of each level of miraculousness In showing the primacy of the Qur’anic text, as well as the sincerity of the prophecy of Muhammad, may God’s prayers and peace be upon him, and the appropriate approach for this research was the descriptive-analytical approach. What is meant by the shortest pronunciation and the finest system, to prove beyond any doubt that the Noble Qur’an has exceeded the ceiling that human eloquence ends with. The